2008
DOI: 10.1158/1078-0432.ccr-07-4085
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Bric-a-Brac Tramtrack Broad Complex Protein NAC-1 in Cervical Carcinomas Seems to Correlate with Poorer Prognosis

Abstract: Purpose: Recent studies have suggested a novel oncogenic role of a bric-a-brac tramtrack broad complex (also known as POZ) domain gene, NAC-1, in ovarian carcinomas. The aim of this study was to clarify the functional role of NAC-1in human cervical carcinomas. Experimental Design: NAC-1 expression in cervical cancer was assessed by immunohistochemistry, and data on clinical variables were collected by retrospective chart review. NAC-1 gene knockdown using small interfering RNA and a NAC-1 gene transfection sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 23 publications
7
36
0
Order By: Relevance
“…Reduction of NAC1 expression resulted in apoptosis in the NAC1 expressing cell lines Ishikawa, HHUA, and JHEM2, indicating that NAC1 was essential for proliferation and survival of these cell lines. These results are similar to those obtained in our previous experiments in ovarian and cervical cancer cell lines (17,20). Besides its critical role in maintaining cell proliferation and survival, NAC1 overexpression could also enhance cellular proliferation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Reduction of NAC1 expression resulted in apoptosis in the NAC1 expressing cell lines Ishikawa, HHUA, and JHEM2, indicating that NAC1 was essential for proliferation and survival of these cell lines. These results are similar to those obtained in our previous experiments in ovarian and cervical cancer cell lines (17,20). Besides its critical role in maintaining cell proliferation and survival, NAC1 overexpression could also enhance cellular proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…NAC1 is a transcription repressor that is involved in self renewal and the maintenance of pluripotency in embryonic stem cells (18). NAC1 is significantly overexpressed in several types of human carcinomas (17), where it plays a critical role in maintaining tumor cell proliferation and survival (17,(19)(20)(21). Recently, we showed that NAC1 is essential for the proliferation of normal cyclic endometrial glandular cells and is up-regulated by estrogen (22).…”
Section: Introductionmentioning
confidence: 99%
“…NAC1 expression was essential for growth and survival in the normal endometrium. Because NAC1 is considered to have oncogenic potential (11,14,20), the current findings may provide new insight into understanding the mechanism behind estrogen-induced endometrial carcinogenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we reported that NAC1, a gene with oncogenic potential, was associated with gynecologic tumors (11,14,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation